Production of Essential Oil from Sakura Flowers (Prunus serrulata) at Cibodas Botanical Garden - Zahid, Mohamad Ghazwani; Azka, Shyfan Haidar; Faiza, Muhammad Octa; Assyakur, Adli Abdurrahman; Alghifari, M. Daffah; Taufik, Agung; Hidayat, Andri Syarif (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Essential oils are aromatic compounds produced by plants and widely used in cosmetics, perfumes, pharmaceuticals, and aromatherapy due to their bioactive properties. Sakura flowers (Prunus serrulata) contain phenolic and aromatic compounds with potential antioxidant and aromatic value. This study aimed to produce essential oil from sakura flowers collected at Cibodas Botanical Garden and to analyze its physical and aromatic characteristics. An experimental descriptive method was applied using steam distillation with a Clevenger apparatus. Fresh sakura flowers were processed to obtain essential oil, and the resulting product was evaluated based on yield, color, aroma, density, and refractive index. The results showed that the essential oil yield ranged from 0.2–0.5% (v/b) with a pale yellow to golden color and a characteristic floral aroma. These findings indicate that sakura flowers from Cibodas Botanical Garden have potential as a source of essential oil and may be utilized for cosmetic, aromatherapy, and fragrance applications.